Mental Health, Alcohol and Substance Use of Refugee Youth - Vasic, Jelena; Grujicic, Roberto; Toskovic, Oliver; Pejovic Milovancevic, Milica (Frontiers in Psychiatry, 2021)
This study aims to explore the prevalence of alcohol and substance use among young refugees along with the indicators of experienced psychological difficulties. It is based on a sample of 184 children and adolescents aged 11–18 years old, residing at two refugee centers in the Republic of Serbia. Out of 184 participants, the majority was male (N = 155; 84.29%). More than a half of participants (53.3%) displayed significant symptoms of PTSD. 50% consume energy drinks, 28% use tobacco; 13% use alcohol; 4.6% use marijuana; 1.7% use LSD, amphetamines, glue, tranquilizers and cocaine. Female respondents were more frequently expressing emotional difficulties (p < 0.05) while male participants were more frequent users of alcohol or substances (p < 0.01). Younger children were more frequently expressing symptoms of hyperactivity and prosocial behavior, while they were less frequently using substances. There is also a significant negative correlation between the years of education and individual proneness to substance use. Furthermore, those who resided in a greater number of refugee camps were found to experience greater levels of emotional and behavioral difficulties and face a greater risk of physical abuse. The burden of migration increases proneness to substance use, as a consequence of scarce coping resources and the stress of adjusting. Migrants are vulnerable to substance use, since some of them have commonly witnessed and/or personally experienced pre-and post-migration stress and trauma, including loss of homes and livelihoods, violence, torture and family separation. Preventive programs need to focus on the problem of alcohol and substance use among this vulnerable population.